Magnetohydrodynamic Calculations of Toroidal Fusion Reactor to Ensure Stable Control - Hançerlioğullari, Aybaba; Kurnaz, Asli; Madee, Yosef G. Ali (Scientific Research Publishing, Inc., 2016)
The development of magnetic configurations to confine the stability fluid plasmas for fusion energy is a challenge that is a mixture of basic fusion engineering and invention. In order to keep the fusion reactions in the plasma to be continuing in the fusion reactors, the speed of tritium breeding (TBR) should be kept above a certain value. At the Apex fusion reactor, a fast flowing thin liquid wall has replaced the solid first wall concept of the traditional reactors. Behind the fast flowing thin liquid wall, a slower and thicker second liquid wall (coat) is present. Monte Carlo Random method (MCRS) is the general name for the solution of experimental and statistical problems with a random approach. This method is dependent upon the theory of probability. In the present work, Mhd impacts are investigated quite unimportant for Flibe salt solutions. In this study, the fissile fuel production calculations are done for a neutron wall load of 10 MW/m2 fissile fuel production rates of 238U(n, γ)239Pu and 232Th(n,γ)233U increases almost linearly with increased heavy metal content.
Keywords: 7. Clean energy; 3. Good health